2011
DOI: 10.1080/02786826.2010.531300
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Monodisperse, Singly Charged Nanoparticles through Polydisperse Fibrous Filters

Abstract: The article presents experimental results and theoretical analysis of aerosol nanoparticle penetration through fibrous filters with a broad fiber diameter distribution. Four fibrous filters were produced using the melt-blown technique. The analysis of the filters' SEM images indicated that they had log-normal fiber diameter distribution. Five kinds of proteins and two types of silica particles were generated by electrospraying and were then classified using a Parallel Differential Mobility Analyzer to obtain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Matulevicius et al (2014) experimentally measured the collection performance of nanofiber filter media fabricated by electrospinning of polyamide, and reported that the filter with finer fibers had a high collection efficiency and a high quality factor. Sambaer et al (2014) and Podgorski et al (2011) introduced the inhomogeneity factor in the prediction of collection efficiency of a laminated nanofiber filter, which was originally proposed by Kirsch et al (1975), and reported that the predicted collection efficiency agreed well with the experimental data by the correction with the inhomogeneity factor. They also reported that the inhomogeneity factor of nanofiber filter was high compared to HEPA filters.…”
Section: Introductionmentioning
confidence: 68%
“…Matulevicius et al (2014) experimentally measured the collection performance of nanofiber filter media fabricated by electrospinning of polyamide, and reported that the filter with finer fibers had a high collection efficiency and a high quality factor. Sambaer et al (2014) and Podgorski et al (2011) introduced the inhomogeneity factor in the prediction of collection efficiency of a laminated nanofiber filter, which was originally proposed by Kirsch et al (1975), and reported that the predicted collection efficiency agreed well with the experimental data by the correction with the inhomogeneity factor. They also reported that the inhomogeneity factor of nanofiber filter was high compared to HEPA filters.…”
Section: Introductionmentioning
confidence: 68%
“…Podgorski (2009) derived a numerical method to compute the penetration of nanoparticles through inhomogeneous fibrous filters from single fiber filtration expressions corresponding to the Kuwabara flow (Kuwabara 1959). Good agreement was demonstrated in comparison with the experimental data when a proper segregation intensity for the different fibers was used (Podgorski et al 2011). However, the above models were not developed for the net structure of UNFs and the co-existing NFs, which can lead to special characteristics on the filtration performance.…”
Section: Introductionmentioning
confidence: 88%
“…The deposition efficiency for an individual fiber with a diameter d F for a diffusion mechanism E D can be calculated based on numerous correlations described in various sources (Natanson, 1957;Stechkina and Fuchs, 1966). However, the best results were obtained from the relationship that was a combination of correlations from the quoted works which took the following form (Podgórski et al, 2011):…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…The influence of a number of very important factors on the course of the nanofiltration process was tested, including the size of aerosol particles, their morphology, the velocity of aerosol flow through the filter and the structure of the separating material. In addition, the obtained data were interpreted using the classical theory of filtration (Hinds, 1999), which states that the Brownian diffusion is the dominant mechanism for determining the filtration efficiency of nanoparticles, and the Partially Segregated Flow Model (Podgórski, 2009;Podgórski et al, 2011;Jackiewicz et al, 2013) proposed by our research group. Up to now, the model was examined whether it can be used to describe the process of separation of sub-micron and micron-sized solid particles and monodisperse nanoparticles.…”
Section: Introductionmentioning
confidence: 99%